Save Your Data, Save Your Money"Schools Safe From Phishing and Scams" - Asep Ririh Riswaya; Suwandana Suryana Putera; Aep Syaripudin; Agni Ahmad Saripudin; Alfi Yudin Raihan; Aris Koharudin Farras; Muhammad Naufal; Sandri Arya Fikriawan; Septian Adiraharja; Sigit Aprilian; Sirozudin Ibnu Farhan (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
In an increasingly sophisticated digital age, information security, or cybersecurity, has emerged as a significant challenge that is frequently misunderstood by the public, particularly among demographics with limited exposure to technology.  An illustrative instance is evident in the Yayasan Badru environment, where participants exhibit inadequate comprehension of the perils associated with the digital realm and the measures to avert cybercrime.  The primary objective of this educational activity is to impart a fundamental comprehension of cybersecurity, equipping participants to identify diverse digital threats, grasp prevalent terminology in the cybersecurity domain, and recognize applicable prevention strategies for their daily digital engagements. This exercise employs a qualitative methodology that includes direct observation and active engagement with participants.  The material is presented in an accessible manner, customized to the participants' understanding, addressing subjects including phishing, malware, personal data theft, and secure browsing practices.  The findings of this activity demonstrate an enhancement in participants' awareness and attentiveness concerning diverse types of digital crime.  Participants have adopted a more prudent approach to utilizing digital devices and may use fundamental cybersecurity principles in their daily lives In conclusion, cybersecurity education has demonstrated efficacy in enhancing digital literacy and providing preliminary protection for the community against the hazards associated with technological growth.  This education must be ongoing to develop a secure, risk-conscious digital society prepared to confront future difficulties in the online realm.